La sociedad civil como posible respuesta a la crisis del Estado de Bienestar europeo y sus limitaciones en el caso español - Juárez, Miguel (Miscelánea Comillas, 2005)
The principal objective of this article is twofold. On one hand, it presents Civil Society as a possible response to the crisis in the State of European Social Welfare, taking as central point the scientific positions of Claus Offe, Pierre Rosavallon, and Alan Wolfe towards the end of the 20th century. And on the other hand, the article tests its possible limitations in the Spanish situation.